Labour brokers under section 198 of the Labour Relations Act after Assign Services v NUMSA 2018 (5) SA 323 (CC) - Anderson, Shaun (University of the Witwatersrand, Johannesburg, 2024)
This research will focus on Temporary Employment Services (“TES”) in South Africa, more commonly known as labour brokers and will consider the 2014 related amendments in legislation and the case of Assign Services v NUMSA 2018 (5) SA 323 (CC) which arose and set the precedent for the future of labour brokers in South Africa. The Labour Relations Amendment Act 6 of 2014 (“LRA”) and the Basic Conditions of Employment Amendment Act 20 of 2013 (“BCEAA”) were both passed into law and will have an effect on the TES relationship within South Africa. Trade unions and many civil society organisations have called for the banning of TES in South Africa. The South African government, rather than banning them, decided to amend the existing laws regarding TES in order to regulate them further and provide employees with more job security. This research report will focus on the regulation of TES in South Africa, the nature and implications of the LRA on TES in South Africa after the Assign Services v NUMSA case. The research report will offer conclusions on the impact of the amendments and thoughts on improvements for the future. In terms of the LRA and Sections which regulate TES employment as well as the Assign Services v NUMSA case, this research will consider what affect the amendments and case had on the TES relationship. It will identify problems that were associated with the case and how the case impacted on TES within South Africa as well as discuss any gaps in the legislation that can be identified and how to possibly address these issues in conclusion.
A research report submitted in fulfillment of the requirements for the Master of Laws, in the Faculty of Commerce Law and Management, School of law, University of the Witwatersrand, Johannesburg, 2025
Keywords: UCTD; Labour brokers; section 198; Labour Relations Act; NUMSA 2018 (5) SA 323 (CC); SDG-8: Decent work and economic growth; SDG-16: Peace, justice and strong institutions